Too much love in the neighborhood can hurt: how an excess of intensity and trust in relationships may produce negative effects on firms - Molina‐Morales, F. Xavier; Martínez‐Fernández, M. Teresa (Strategic Management Journal, 2009)
This study aims to provide a better understanding of the effect of social networks on innovation through the analysis of territorial agglomerations of firms. Critical voices argue that the same mechanisms that form the basis of efficient, continuous improvements of clustered firms can also be considered as limitations. We suggest that the impact of social capital decreases beyond a certain point of development. In fact, the effect of social interactions and trust on firm value creation can be described as an inverted U‐shaped curve. The study is based on a sample of 154 firms in the Valencia region of Spain. Implications of the study have relevant prescriptions for regional planners and individual entrepreneurs. Copyright © 2009 John Wiley & Sons, Ltd.